Makna Simbolik Ayat-Ayat tentang Kiamat dan Kebangkitan dalam Al-Qur'an - Andy Hadiyanto; Umi Khumairoh (Universitas Negeri Jakarta, 2018)
This research aims to get a symbolic understanding of the meaning of the doomsday and resurrection in the Qur'an (eschatological verses) with textual and contextual analysis of these verses. The eschatological verses in the Qur'an beside having textual-theological meanings have symbolic meanings. Theological meanings presupposes that the events of the apocalypse, the resurrection, the life of heaven and hell are the areas of faith that must be believed to be a real event of a supernatural nature. While symbolic meanings menyaran on the understanding that the verses are diuturnkan in the context of culture and situation of certain historical conditions that allow the reading of eschatological concepts are contextual. The research uses literature approach and literature review method that is used is structural analysis, based on the theory that the text of al-Qur'an consists of various elements forming the structure. This research also uses descriptive qualitative research approach with survey research method. The survey method is used to describe PAI lecturer's understanding of the symbolic meaning of eschatological verses in the Qur'an